Design and analysis of concrete pump truck with carbon fibre composite placing boom. (May 2015) - Hu, Y.; Xu, S.; Zhang, J.; Ding, G.; Zhou, Z.; Fang, Y.
<x content-type="archive" xml:space="preserve">Abstract</x> Traditional concrete pump trucks are made of high-strength alloy steel, which causes serious welding defects. Carbon fibre composites have high strength, light weight and are good candidates for the design of concrete pump truck placing booms. As the boom operates in a complex alternating stress state, it is designed into two parts in this article. The first part is the beam structure of carbon fibre boom, which is designed and analyzed with finite-element software ANSYS. The results show that it meets the requirements of strength and stiffness when the layer depth is 15 layers, and the stacking sequence is [02/45/08/ −45/03]. The second part is boom end, which is designed as metal encapsulated carbon fibre composites sandwich structure. Finally, the stepped lap joint is chosen to connect the two parts; its parameters are determined, and the shear strength of the bonding layer is verified.